Bank selection criteria employed by undergraduates in Malaysia / Shahreena Daud, Zarinah Abu Yazid and Nur Asyira Naziron - Daud, Shahreena; Abu Yazid, Zarinah; Naziron, Nur Asyira (Research Management Institute (RMI), 2012)
Banking industry in Malaysia are now providing a wide range of services and investing a large amount of money in marketing strategies and promotional activities in order to attract and retain customer. In this competitive market, it is imperative that banks be aware of the factors or determinants that their customer consider important when selecting a bank. This study will investigate the selection criteria employed by undergraduates in UiTM Melaka, how these criteria are prioritized according to their importance and also to examine the different of bank selection criteria among gender. In analyzing the data, this study relied on 30 selection factors from Almossawi (2001) and used Varimax rotation factor as a tools. The result from the survey on 207 undergraduates indicated that they ranked 24 hours availability of ATM ( Automated teller machine) service as the most important criteria, meanwhile banks open during Friday prayer was given the lowest ranking. Based from gender, male indicated that availability of ATM in several locations as the most important criteria while female indicated that 24 hours availability of ATM service as the most important determinant too. Both gender agreed that bank opens during Friday prayer was the lowest ranking. Seven factors group were developed from factor analysis. Since undergraduates are among the potential customer for bank industry, it is recommended that banks should focus on financial benefits, location and facilities as their strategies in order to attract new customer. Furthermore, recommendation for future research have also been put forth in this study.